Research on the state of the surface layers of parts of tribological systems coercimetric method - Аулін, В.В. (Problems of Tribology, 2015)
The method of measuring the coercive force. The possibilities coercimetric method in the analysis of stress-strain state of the surface layers of parts of tribological systems: the construction of the nomogram; stress analysis I-III kind; construction of cartograms to select a range of values of the coercive force characteristic of the various states; dependence of the coercive force of the applied load and classification of modes of operation; statistical distribution of the coercive force and determination of residual life. Given the experimental results of the stress-strain state components of tribological systems CPG diesel КамАЗ-740. The results given the wear condition and the stress-strain state in the coercive force, built cartograms coercive force distribution along the generatrix of the cylinder liners and the angle of the sector of the cross-section if the service life of diesel mobile agricultural machinery in 1600 moto-h., 3150 moto-h. – without remedial action; 3640 moto-h. – technological and technical regenerates.It is shown that with the combined physical and chemical modification of copper-based engine oil additives with the imposition of the electric and magnetic fields, reducing wear, created equal to the wear work surfaces with a minimum of stress-strain state and the minimum orthographic wear, lengthens life CPG parts and diesel engine as a whole.